Escape angles for solitary animals and groups of the lizard Pholidoscelis fuscatus. Issue 2 (4th March 2023) - Eifler, Douglas A.; Eifler, Maria A.; Garrison, Grace E.; Grotbeck, Victoria L.
Abstract : Predation can be an important factor shaping the dynamics of animal groups. The lizard Pholidoscelis fuscatus forms small groups while foraging, providing the opportunity to examine how predation risk influences group dynamics. We studied the escape angles of P. fuscatus during simulated predator approaches, focusing on whether grouped lizards behaved differently from solitary animals and the extent to which group cohesion was maintained during escape. Both solitary and grouped lizards exhibited non-random escape angles, oriented away from the approaching predator. However, lizards in groups exhibited escape angles closer to 0° (i.e., more directly away from the predator) than solitary lizards. Groups maintained their cohesiveness during flight. Grouping by P. fuscatus could allow more effective escape behaviour to occur.